Organizing Fundraising Event: A Qualitative Assessment of Project Plan in Save The Children Phoenix, Arizona - Rudiyanto, Tri; Liiamaa, Jonathan; Toure, Sabine; Afulani, Olivia; Johnstonee, Alexis (Economic and Business Horizon, 2022)
The role of different fundraising strategies in successfully implementing projects has been widely established in areas such as the planning and control of time, cost, and quality. This paper aims to highlight the role of the qualitative method in assessing the project fundraising event in a systematic and sequential manner. It suggests that being constantly aware of identifying the project, constraints, and requirements is valuable for the researcher, the knowledge obtained, and the participant. The discussion not only focuses on the implementation of the project but also focuses on the project plans that, in reality, measure the success of the project, such as scope, budget and cost, staffing, communication, quality, and risk. This fastidiousness and vigilance enhance confidence that this assessment closely reflects the reality of a fundraising event and will bring a higher possibility of project success.